THE EFFECTIVENESS OF BLIND FOLD GAME IN TEACHING SPEAKING AT SEVENTH GRADE STUDENTS OF SMP NEGERI 2 BESUKI IN ACADEMIC YEAR 2015/2016 - Novi Mistiani Mistiani; Yepi Sedya Purwananti; Moh. Hanafi (STKIP PGRI TULUNGAGUNG, 2016)
This article was a complete report of investigation on theeffectiveness of blind fold game in teaching speaking. Speaking is one of the basicskill that requires the process of communicative competence, pronunciation(intonation, stress, and pitch), grammar, fluency, vocabulary and comprehensionin order to build a good communication. English teacher must apply a techniquethat is more interesting and enjoyable in teaching and learning process especiallyin teaching speaking skill. One of the most important reasons for using game issimply that they are immensely enjoyable for both teacher and student. Thisresearch used pre-experimental design. The researcher took one class whichconsists of 23 students as the data of this research. Pre-test and Post-test weregiven to take the score of student’s. All of the data are analyze statistically byusing SPSS. 21.0. The statistical analysis showed that from the table of pairedsample t-test showed that significance is 0.000. So that 0.000 0,05, and t table intable t test t table. 26,785 0,5%. The hypothesis of the research is accepted andimplementing Blind Fold Game is effective as method to engage studentsspeaking.Keyword: Speaking, Blind Fold